"Canada's back" - can the Trudeau government resuscitate Canadian diplomacy? - Copeland, Daryl (Canadian foreign policy journal, 2018)
Canadian Prime Minister Justin Trudeau and his ministers have been fond of emphasizing that "Canada is back" on the global stage. Defense and development reviews have been completed, but, with the exception of Foreign Minister Freeland's brief parliamentary address in June 2017, little is known of the government's intentions regarding international policy, diplomacy or grand strategy. This analysis reviews key developments during the transition from the Cold War to the globalization age, examines Canada's evolving place in the post-war world, and assesses that the performance of the government through to mid-term has been, at best, mixed. To improve results, the author sketches an ambitious five-point plan for fundamental diplomatic, institutional and international policy transformation.